B lymphocyte maturation in Wegener's granulomatosis: a comparative analysis of VH genes from endonasal lesions. Issue 7 (16th November 2005) - Voswinkel, J; Mueller, A; Kraemer, J A; Lamprecht, P; Herlyn, K; Holl-Ulrich, K; Feller, A C; Pitann, S; Gause, A; Gross, W L
Abstract : Background: Anti-neutrophil cytoplasmic antibodies (ANCA) directed against proteinase 3 (PR3) are highly specific for Wegener's granulomatosis (WG). Evidence for a pivotal role of PR3-ANCA in the induction of vasculitis has been demonstrated. B cell clusters have been observed within endonasal biopsy specimens. Objectives: To determine whether B cell selection and maturation take place in granulomatous lesions of WG. Methods: Granulomatous lesions and the immunoglobulin (VH) gene repertoire from nasal tissue of six WG patients—two active and two smouldering localised WG (ANCA negative, restricted to respiratory tract), plus one active and one smouldering PR3-ANCA positive generalised WG—were characterised by immunohistochemistry, polymerase chain reaction, cloning, DNA sequencing and database comparison. Results: B lymphocyte-rich, follicle-like areas were observed proximal to PR3 positive cells and plasma cells in granulomatous lesions; 184 VH genes from these granulomatous lesions were compared with 84 VH genes from peripheral blood of a healthy donor. The mutational pattern of VH genes from active WG resembled memory B cells. Structural homologies of VH genes from granulomatous lesions to PR3-ANCA encoding genes were detected. Significantly more genes (55%, 45%, and 53%, respectively) from active WG compared with the healthy repertoire carried mutations to negatively charged amino acids within the binding site coding regions, favouring affinity to the positively charged PR3. Conclusions: Selection and affinity maturation of potentially PR3-ANCA producing autoreactive B cells may start in granulomatous lesions, thereby contributing to disease progression from ANCA negative localised to PR3-ANCA positive generalised WG.